Evaluation of exchange-correlation functionals for time-dependent density functional theory calculations on metal complexes. - Holland, J; Green, J (2010)
The electronic absorption spectra of a range of copper and zinc complexes have been simulated by using time-dependent density functional theory (TD-DFT) calculations implemented in Gaussian03. In total, 41 exchange-correlation (XC) functionals including first-, second-, and third-generation (meta-generalized gradient approximation) DFT methods were compared in their ability to predict the experimental electronic absorption spectra. Both pure and hybrid DFT methods were tested and differences between restricted and unrestricted calculations were also investigated by comparison of analogous neutral zinc(II) and copper(II) complexes. TD-DFT calculated spectra were optimized with respect to the experimental electronic absorption spectra by use of a Matlab script. Direct comparison of the performance of each XC functional was achieved both qualitatively and quantitatively by comparison of optimized half-band widths, root-mean-squared errors (RMSE), energy scaling factors (epsilon(SF)), and overall quality-of-fit (Q(F)) parameters. Hybrid DFT methods were found to outperform all pure DFT functionals with B1LYP, B97-2, B97-1, X3LYP, and B98 functionals providing the highest quantitative and qualitative accuracy in both restricted and unrestricted systems. Of the functionals tested, B1LYP gave the most accurate results with both average RMSE and overall Q(F) < 3.5% and epsilon(SF) values close to unity (>0.990) for the copper complexes. The XC functional performance in spin-restricted TD-DFT calculations on the zinc complexes was found to be slightly worse. PBE1PBE, mPW1PW91 and B1LYP gave the most accurate results with typical RMSE and Q(F) values between 5.3 and 7.3%, and epsilon(SF) around 0.930. These studies illustrate the power of modern TD-DFT calculations for exploring excited state transitions of metal complexes.